Epigenetic Regulations of Cancer Stem Cells by the Aryl Hydrocarbon Receptor Pathway - Sabah, Akhtar (2020)
Compelling evidence has demonstrated that tumor bulk comprises distinctive subset of cells generally referred as cancer stem cells (CSCs) that has been proposed as a strong sustainer and promoter of tumorigenesis and therapeutic resistance. These distinguished properties of CSCs have raised interest in understanding the molecular mechanisms that govern the maintenance of these cells. Numerous experimental and epidemiological studies have demonstrated that exposure to environmental toxins such as the polycyclic aromatic hydrocarbons (PAHs) is strongly involved in cancer initiation and progression. The PAH-induced carcinogenesis is shown to be mediated through the activation of a cytosolic receptor, aryl hydrocarbon receptor (AhR)/Cytochrome P4501A pathway, suggesting a possible direct link between AhR and CSCs. Several recent studies have investigated the role of AhR in CSCs self-renewal and maintenance, however the molecular mechanisms and particularly the epigenetic regulations of CSCs by AhR have not been reviewed before. In this review, we first summarize the crosstalk between AhR and cancer genetics, with particular emphasis on mechanisms relevant to CSCs such as Wnt/β-catenin pathway, Notch pathway, NF-κB pathway, PTEN-PI3K/Akt pathway and Drug Resistance-mediating pathways. The second part of this review discusses the recent advances and studies highlighting the epigenetic mechanisms mediated by the AhR pathway that control CSC gene expression, self-renewal, and chemoresistance in various human cancers. Furthermore, the review also sheds light on the importance of targeting the epigenetic pathways as a novel therapeutic approach against CSCs.